116 Retrospective Analysis of Clozapine Augmentation in Treatment-Resistant Schizophrenia in an Outpatient Setting. (15th June 2018) - Odom, Charles; Walyzada, Frozan; Manocha, Pankaj; Gashi, Monika; Martin, Ashaki; Cheema, Raminder; Gu, Wen; Shah, Ketki; Korenis, Panagiota
Abstract: Study Objectives: This retrospective analysis hopes to add to the literature about Treatment Resistant Schizophrenia (TRS), augmentation strategies with antipsychotics used in our patient population with the hopes of clarifying what possibilities should be further studied. In addition, we aim to emphasize the need for focusing on individualized treatment and multidisciplinary efforts to ensure compliance and appropriate disposition options. Method: We reviewed retrospectively 3025 charts of patients between January 2017 to March 2017 in our outpatient department establishing which antipsychotic clozapineaugmentation strategies were being used. We also did a literature review to establish what augmentation strategies are recommended. These patients will then be compared to a random sample of patients in the clinic who were not prescribed clozapine and compared for readmission rate, side effect profile, length of stay while admitted, frequency of clinic attendance and compliance with outpatient appointments. Results: Out of 3025 patients 35 were prescribed Clozapine as monotherapy and 5 patients had clozapine plus psychopharmacological augmentation. Ages ranged from 21-86. Out of the 39 patients, there were 13 male and 26 female. The predominant diagnosis was mood disorder or MDD with psychotic features followed by schizophrenia. The augmentation antipsychotics used were aripiprazole and risperidone. In the literature, the most frequent augmentation strategy for TRS is adding another antipsychotic with more D2 receptor blockade. Other strategies involve identifying and treating the symptoms not controlled by clozapine. Conclusions: Currently augmentation of Clozapine in TRS is highly individualized due to lack of supporting evidence to state the contrary. When working with treatmentresistant patients who are not responding to clozapine alone, it is imperative to thoroughly review and consider all treatment options and augmentation strategies. More studies should be done in controlled settings to better evaluate possibilities as well as more evaluations to be done on other ways of augmentation of clozapine. Literature has stated between 20-60% of patients are defined as TRS. Clozapine is considered as one of the most effective treatment available at present time for TRS. Recent literature suggests despite its superior efficacy, as many as 70% of those suffering from TRS on clozapine continue to suffer from positive, negative or cognitive symptoms. The literature has abundant adjunctive treatment strategies such as the addition of antipsychotics, mood stabilizers, antidepressants, or even with the use of electroconvulsive therapy. We emphasize the importance of correctly identifying TRS patients who may benefit from the initiation of clozapine, what would be beneficial for them if they do not respond, how to tailor their treatment to target symptoms not being ameliorated, and recommend treatment in these complex cases be multidisciplinary. Funding Acknowledgements: No funding.